Atherosclerosis is Evident in Treated HIV-Infected Subjects With Low Cardiovascular Risk by Carotid Cardiovascular Magnetic Resonance. (15th April 2016) - Rose, Kathleen A. M.; Vera, Jaime H.; Drivas, Peter; Banya, Winston; Keenan, Niall; Pennell, Dudley J.; Winston, Alan
Abstract : Objective: Premature atherosclerosis has been observed among HIV-infected individuals with high cardiovascular risk using one-dimensional ultrasound carotid intima-media thickness. We evaluated the assessment of HIV-infected individuals with low traditional cardiovascular disease risk using cardiovascular magnetic resonance, which allows three-dimensional assessment of the carotid artery wall. Methods: Carotid cardiovascular magnetic resonance was performed in 33 HIV-infected individuals (cases) (19 male, 14 female), and 35 HIV-negative controls (20 male, 15 female). Exclusion criteria included smoking, hypertension, hyperlipidemia (total cholesterol/HDL ratio > 5) or family history of premature atherosclerosis. Cases were stable on combination antiretroviral therapy with plasma HIV-1 RNA <50 copies per milliliter. Using computer modeling, the arterial wall, lumen, and total vessel volumes were calculated for a 4-cm length of each carotid artery centered on the bifurcation. The wall/outer-wall ratio (W/OW), an index of vascular thickening, was compared between the groups. Results: Cases had a median CD4 cell count of 690 cells per microliter. Mean (±SD) age and 10-year Framingham coronary risk scores were similar for cases and controls (45.2 ± 9.7 years versus 46.9 ± 11.6 years and 3.97% ± 3.9% versus 3.72% ± 3.5%, respectively). W/OW was significantly increased in cases compared with controls (36.7% versus 32.5%, P < 0.0001); this was more marked in HIV-infected females. HIV status was significantly associated with increased W/OW after adjusting for age ( P < 0.0001). No significant association between antiretroviral type and W/OW was found—W/OW lowered comparing abacavir to zidovudine ( P = 0.038), but statistical model fits poorly. Conclusions: In a cohort of treated HIV-infected individuals with low measurable cardiovascular risk, we have observed evidence of premature subclinical atherosclerosis.